2001
DOI: 10.1091/mbc.12.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Cycle Progression by Swe1p and Hog1p Following Hypertonic Stress

Abstract: Exposure of yeast cells to an increase in external osmolarity induces a temporary growth arrest. Recovery from this stress is mediated by the accumulation of intracellular glycerol and the transcription of several stress response genes. Increased external osmolarity causes a transient accumulation of 1N and 2N cells and a concomitant depletion of S phase cells. Hypertonic stress triggers a cell cycle delay in G2 phase cells that appears distinct from the morphogenesis checkpoint, which operates in early S phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 53 publications
6
75
0
6
Order By: Relevance
“…The assumption behind this approach was that osmotic stress-signaling pathways control two responses, one delaying the cell cycle and the other allowing response and adaptation to stress. This idea is consistent with similar studies done in S. cerevisiae (Alexander et al, 2001), where the glycerol-based osmoregulation mutants were used to analyze the role of Swe1 and Hog1 in cell cycle regulation after hyperosmotic stress. Taken together, the results indicate that Srk1 is not part of the rapid stressadaptation response, but that it is necessary to coordinate cell cycle progression under stress.…”
Section: Srk1 Kinase As a Component That Coordinates Stress Response supporting
confidence: 87%
“…The assumption behind this approach was that osmotic stress-signaling pathways control two responses, one delaying the cell cycle and the other allowing response and adaptation to stress. This idea is consistent with similar studies done in S. cerevisiae (Alexander et al, 2001), where the glycerol-based osmoregulation mutants were used to analyze the role of Swe1 and Hog1 in cell cycle regulation after hyperosmotic stress. Taken together, the results indicate that Srk1 is not part of the rapid stressadaptation response, but that it is necessary to coordinate cell cycle progression under stress.…”
Section: Srk1 Kinase As a Component That Coordinates Stress Response supporting
confidence: 87%
“…Recently, p38a/b2 have been implicated in control of the spindle assembly checkpoint in Xenopus oocytes (Takenaka et al, 1998), whilst the budding yeast p38 homologue, Hog1p, mediates a G 2 delay in response to osmotic stress (Alexander et al, 2001). In addition, p38g is required for a g-radiation mediated G 2 arrest in mammalian cells (Wang et al, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…sln1 ts4 , Pbs2 DD ) result in arrest of cell cycle progression (Alexander et al, 2001;Belli et al, 2001;Yaakov et al, 2003;Escote et al, 2004). It has been reported that activated Hog1 leads to G 1 arrest by a dual mechanism that involves downregulation of cyclin expression and direct phosphorylation of the CDK-inhibitor protein Sic1.…”
Section: Introductionmentioning
confidence: 99%